3D Printing of Ion Optics for Electric Propulsion - Guo, Ning; Xie, Kan; Sangregorio, Miguel; Wang, Ningfei; Zhang, Zun; Gabriel, Stephen B. (Frontiers in Physics, 2019)
Additive manufacturing is rapidly opening its way into many areas of the aerospace industry, where different 3D printing technologies are finding niche applications in which they do not only simplify the process and allow shorter lead times, but also the particularities of these new fabrication methods yield new material properties that enhance the component and can lead to higher performance and longer service life of an aerospace system. Although rapid manufacturing processes are being tested for in-space manufacturing and are commonly used to fabricate UAV parts and some spacecraft subsystems with 3D printed components have been tested in space, little research has been conducted on the potential application of these techniques to electric thrusters. This paper presents the study conducted on the application of selective laser melting, a powder bed fusion technology, to the fabrication of ion engine grids and the challenges faced during the process. The first proof of concept and its optimization are described. Later, the development of the selective laser melting process for molybdenum, the study of the 3D printed materials' properties, their direct application to ion extraction systems, and the tests of additively-manufactured ion optics are described. It was found that 3D printed grids can be accurately fabricated with titanium and molybdenum, that they perform similar to conventional optics in short tests, that the selective laser melting process allows certain control of the coefficient of thermal expansion of the output and that this fabrication method allows the reproduction of sputtering erosion patterns. Future research in this direction will cover sputtering tests of selectively-laser-melted samples and the additive manufacturing of carbon-carbon grids.